The effect of organic amendments on soil microbial activity and yield of faba bean (Vicia faba) inoculated with Rhizobium leguminosarum - MOSAVI-AZANDEHI, SEYED MORTEZA; ANSARI, MOHAMMAD HOSSEIN; SHARIFI, PEYMAN; HOOR, SHAHRAM SEDAGHAT (The Indian Journal of Agricultural Sciences, 2023)
A two year (2021 and 2022) field experiment was conducted to study the effect of organic amendments on soil microbial activity and yield of faba bean (Vicia faba L.) inoculated with Rhizobium leguminosarum at Savadkuh in the north of Iran as a factorial experiment based on a randomized complete block design with 3 replications. The treatments included seed inoculation at two levels (inoculation with Rhizobium leguminosarum bv. Viciae and non-inoculation) and fertilization at 5 levels [cattle manure (CM) @30 tonnes/ha, vermicompost of manure (VM) @20 tonnes/ha, vermicompost of Azolla (VA) @20 tonnes/ha, chemical fertilization based on soil analysis (NP), and control]. Present study found that the soil microbial biomass carbon (C) increased over time until 120 daysafter emergence (DAE). The maximum microbial biomass-C (441 mg/g soil) and bacterial count (545 × 105 cfu/ml) were obtained from the inoculated VA treatment. The highest yields of pods (14400 kg/ha) and seeds (1266 kg/ha) were obtained when the use of vermicompost was accompanied by inoculation of R. leguminosarum, so that in plants without inoculation, the use of vermicompost increased the yield of pods compared to the NP by 34% and compared to CM, it increased by 44%, but this increase was 39% and 19% for inoculated plants compared to NP and CM, respectively. Although the seeds of vermicomposted plants showed lower iron (Fe) content, they showed higher nitrogen (N), phosphorus (P), copper (Cu) and zinc (Zn) content than other plants. In total, the results showed a significant improvement in soil microbial activity, absorption of nutrients and bean yield by using vermicompost(especially VA) under R. leguminosarum inoculation. Therefore, in the low-fertile soils of Iran, the combined use of high-quality vermicompost together with R. leguminosarum can strengthen soil microbial activity and bean production and be a suitable alternative to chemical fertilizers.